2001
DOI: 10.1002/ecjb.1021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of new‐mode‐type SAWs by procedures combined with finite‐element and analytical method, and their applications for devices used in mobile communications

Abstract: SUMMARYSimulations using a combination of the finite-element method and the analytical method as well as experiments are used to study new-mode-type SAWs. First, in 171°YZc-LiNbO 3 , it is found that there exists a longitudinal leaky SAW with a high acoustic velocity and a high Q in a grating structure with an Al film thickness of 0.084 wavelength. The acoustic velocity is 6100 to 6500 m/s and the Q values are more than 4000 (computed) at both the resonance and antiresonance points. These excellent properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…12 shows a chip photograph of a 170-MHz SAW resonator used in the VCO for industrial wireless terminals. Figure 14 shows characteristics of the 170-MHz VCO using the present SAW resonator [13]. Each SAW resonator is sealed in an SMD package with 3.8 mm square (in the right-hand photo) and is extremely small in size as a resonator in this frequency range.…”
Section: Test Results Of Saw Resonator and Vcomentioning
confidence: 99%
See 2 more Smart Citations
“…12 shows a chip photograph of a 170-MHz SAW resonator used in the VCO for industrial wireless terminals. Figure 14 shows characteristics of the 170-MHz VCO using the present SAW resonator [13]. Each SAW resonator is sealed in an SMD package with 3.8 mm square (in the right-hand photo) and is extremely small in size as a resonator in this frequency range.…”
Section: Test Results Of Saw Resonator and Vcomentioning
confidence: 99%
“…3, the Al-electrode thickness dependence of each resonant mode of the SAW resonator is plotted [13]. 3, the Al-electrode thickness dependence of each resonant mode of the SAW resonator is plotted [13].…”
Section: Grating Mode and Electrode Finger Film Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…A Love-wave-type SAW propagating on a 15°-rotated Y-cut X-propagation LiNbO 3 substrate exhibits extremely strong piezoelectric characteristic and the Love-wave SAW in a device with Au electrodes is reported to provide a wide variable-oscillation range [3]. A 150-MHz VCO using a Love-wave SAW propagating on a grating formed with thick Al films has been reported to provide both wide variable range of oscillation frequency and high C/N [6], and a Love-wave SAW filter in a device with Cu electrodes has been reported to have an extremely wide bandwidth [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the propagation characteristics of the Love-wave SAW and Rayleigh-wave SAW are studied by simulation and experiments. Studies of the suppression of spurious responses caused by degenerate Rayleigh-wave SAW, test fabrication of a SAW resonator for a VCO with spurious responses eliminated, and trial fabrication of a wideband SAW-VCO are reported in this paper [9]. Figure 1 shows the impedance characteristics of a SAW resonator with spurious responses.…”
Section: Introductionmentioning
confidence: 99%